Stigma in adults with sickle cell disease and family members: Scale development and pilot study in the USA and Nigeria - Robin R. Leger; Linda D. Wagner; Victoria Odesina (Elsevier, 2018)
Background: Sickle cell disease associated stigma impacts health-related quality of life and community participation. Stigma in adults living with sickle cell disease and family members was appraised via a pilot study for paired (adult and family) instrument development, face validity, and psychometrics. Methodology: Likert type stigma scales were adapted from epilepsy and HIV literature with Bronfenbrenner's Ecology of Human Development Theory as the conceptual framework. Findings: 42 adults from United States and Nigeria participated in the study. Chronbach's alpha of the 40 item Stigma in SCD Scale(s) = 0.86. Total score 0-120; mean = 40.6, SD = 20.9, range = 4-86. Nigerians report higher stigma (r = .60, p < .01). Adults from both countries "fear that their significant others will reject them" (r = .44, p < .01) and from the US that "service providers do not believe that people with Sickle cell disease have disabilities" (r = .57, p < .01). Factor analysis indicated four interpretable factors: societal impact regarding the disease and isolation; personal feelings of shame, rejection, guilt; treatment when in pain and concerns for the future; and a sense of burden and needing assistance. Conclusion: Tools to assess stigma in adults with sickle cell disease are useful in individuals and family/social supports across cultural populations. The Conceptual model highlights the complexity of systems that can affect stigma. Implementation of the tool can identify issues such as isolation, fear and burden. Further development and analysis is needed to influence education, treatment, and policy. Keywords: Community Based Participatory Research, Ecology of Human Development, Family measures, Instrument development, Sickle cell disease, Social support, Stigma